(untitled) (Architecture Image Studies, 2026)
This study explores the current state of media impact analysis on health communication through a comprehensive bibliometric review of scholarly research. A systematic review was conducted utilizing tools such as VOSviewer, Biblioshiny (R-package), and Publish or Perish, analyzing data from the Scopus database. A total of 248 ournal articles published between 1959 and 2026 were reviewed, revealing a significant increase in publications over the last decade. The analysis highlights the growing importance of social media, health communication strategies, and digital platforms in influencing public health outcomes. Key themes such as crisis communication, public health engagement, social media’s role in health messaging, and mental health communication were consistently found in the literature. The United States, the United Kingdom, and Australia are the leading contributors to this research, with prominent institutions such as Harvard University and the University of California driving substantial scholarly output. Major journals, including Health Communication and Journal of Health Communication, have significantly shaped the field. Additionally, the study emphasizes the crucial role of digital health communication in times of crisis, particularly in managing health information during pandemics like COVID-19. Despite the growing body of research, gaps remain in addressing the effectiveness of communication strategies for marginalized communities and specific health topics. The findings suggest that future research should focus on the integration of new media technologies, social determinants of health, and the impact of personalized communication strategies, offering valuable insights into the evolving landscape of health communication and its role in improving public health.